Eksistensi Solidaritas Sosial Budaya Maudu Lompoa Dalam Tinjauan Geografi Budaya - Hendra -; Budijanto -; I Nyoman Ruja; M. Iqbal Liayong Pratama (Jurnal Azimut, 2019)
The purpose of the research is to describe the existence of maudu lompoa sociocultural solidarity in a review of cultural geography. The life of the community has undergone many shifts in lifestyle, especially individual and meterialistic attitudes, of course if this continues to occur it will cause social conflicts. Therefore, it is necessary to implement the values ​​of solidarity in people's lives. Values ​​derived from national identity so that people's lives run with peace and prosperity. These values ​​reside in many local cultures run by the community. In the Cikoang community, the values ​​of social solidarity are still well preserved in the procession of the Culture of the lompoa. This research is a descriptive study with an ethnographic approach. The results of the study show that the cultural change of maudu lompoa which is influenced by the environmental, social and economic conditions of the Cikoang community turned out to further strengthen the social and cultural solidarity of the people from time to time. The existence of Cikoang community social solidarity in maudu lompoa culture is able to be implemented in daily life.